Evaluation of the prevalence and location of bifid mandibular canals. A CBCT study - Rodrigo Montezano da Cunha; Mariana Boessio Vizzotto; Paula Nery Ignácio Xavier; Priscila F. da Silveira Tiecher; Nádia Assein Arús; Luize Severo Martins; Danielle Bianca de Lima Freire; Heraldo Luis Dias da Silveira (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2021)
Aim: To investigate the prevalence and location of bifid mandibular canals (CMB) using cone beam computed tomography (CBCT). Materials and methods: Three trained and calibrated dental radiologists individually evaluated 1254 CT scans using the I-Cat Vision software (Imaging Sciences International®) and classified them into four distinct types (Retromolar, Dental, Forward and Bucolingual). Frequency data, collected from an Access form (Microsoft® Office), were analyzed using the Fischer and Friedman test. The level of statistical significance was set at 5%. Results: CMBs were found in 276 cases (22%), with no gender predilection (P = 0.186). There was a statistically significant difference between the types (P = 0.001). Discussion: The recognition of a CMB is of great relevance when associated with anesthetic and surgical procedures in the posterior region of the mandible. Although many studies have shown that CMB is not commonly seen, a failure to identify it can result in damage to the lower alveolar nerve (NAI) or difficulty in obtaining anesthetic block. Conclusion: The most frequent type of CMB in both genders was retromolar (P = 0.001), representing 18.5%, and visualized with rates of 47.1% in women and 52.9% in men. The frequency of CMBs analyzed using the CBCT was significant in the population evaluated and presented in different configurations. Thus, its investigation should not be neglected in the face of surgical procedures that involve the posterior region of the mandible.